Opsonins and Dysopsonins of Nanoparticles: Facts, Concepts, and Methodological Guidelines - Papini, Emanuele; Tavano, Regina; Mancin, Fabrizio (Frontiers in Immunology, 2020)
Understanding the effects mediated by a set of nanoparticle (NP)-bound host biomolecules, often indicated with the umbrella term of NP corona, is essential in nanomedicine, nanopharmacology and nanotoxicology. Among the NP-adsorbed proteome, some factors mediate cell binding, endocytosis and clearing by macrophages and other phagocytes (opsonins), while some others display few affinity for the cell surface (dysopsonins). The functional mapping of opsonins and dysopsonins is instrumental to design long-circulating and nanotoxicologically-safe next generation nanotheranostics. In this review we critically analyze functional data identifying specific proteins with opsonin or dysopsonin properties. Special attention is dedicated to: 1) the simplicity or complexity of the NP proteome and its modulation 2) the role of specific host proteins in mediating the stealth properties of uncoated or polymer-coated NPs 3) the ability of the innate immune system, and in particular of the complement proteins, to mediate NPs clearance by phagocytes. Emerging species-specific peculiarities, differentiating humans from preclinical animal models (the murine especially), is highlighted throughout this overview. The operative definition of opsonin and dysopsonin and the measurement schemes to assess their in vitro efficacy is critically re-examined. This provides a shared and unbiased approach useful for NP opsonin and dysopsonin systematic identification.